USING ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) DURING THE CLASS IN ENGLISH LANGUAGE TEACHING AND LEARNING (Conferencea, 2022)
The primary aim of this article is to demonstrate the importance of advanced technologies in teaching and acquiring the English languages. “A new age demands a new paradigm” – Walter McKenzie. People even couldn’t imagine about technological changes in a sphere of teaching 100 years ago. Although English is a native language of British, it has been established as a second language in many countries, namely in India, Nigeria, Ghana and so on. Thus there is a high percentage of demand for acquiring this language all over the world.